A community‐based cross‐sectional survey of medication utilization among chronic disease patients in China. (29th November 2016) - Strand, Mark A.; Gramith, Kirstin; Royston, Macy; Wang, Xiaoxi; Perry, Judith; Elliott, Curt
Abstract: Objectives: To determine medication use patterns and associated health outcomes in Chinese individuals with diabetes, hypertension or hyperlipidaemia. Methods: This community‐based cross‐sectional study was done in a north China city of 300 000 people. Participants were recruited by poster and phone call through Community Health Centres. Data were collected on 638 Chinese individuals. Interviews were done to screen for disease and health behaviours. Fasting blood was collected and analyzed. Key findings: Participants' average age was 52 years. Self‐reported prevalence of type 2 diabetes, hypertension and hyperlipidaemia was 9.6, 29.9 and 20.5% respectively. Medication adherence was found among 88, 60 and 81.5% of individuals with diabetes, hypertension and hyperlipidaemia respectively. Treatment success, as defined by medication adherence and treatment to goal was achieved by 21, 23 and 10% of diabetic, hypertensive and hyperlipidaemic patients. Conclusions: A large proportion of individuals with chronic disease in this China‐based study were not being successfully treated, putting them at high risk for poor health outcomes. In this urban China setting, healthcare services need to be strengthened in order to achieve better treatment outcomes among chronic disease patients. It is recommended that community pharmacists contribute to improving these outcomes through participation in patient education, medication reconciliation and disease state management.